The social commerce: A quantitative analysis of the effects to the students buying behavior in Pamantasan ng Lungsod ng Maynila - Abenoja, Jona S., Busante, Alvin Kent S., Fondevilla, Richiel Joy A., Torres, Mikee A., Villavelez, Jovy J. 4 0 16; 5 (2023)
Abstract This research study aims to examine the impact of social commerce on student buying behavior at Pamantasan ng Lungsod ng Maynila. Specifically, the study focuses on the effects of various social commerce platforms used by students, including Facebook, Instagram, and TikTok. The sample consisted of 186 Marketing students selected through random sampling from a total population of 602. Data treatment and analysis were conducted using percentage, weighted mean, and ANOVA analysis. The results indicate both positive and negative effects of social commerce on student buying behavior. The positive effects received an overall mean score of 3.85 (interpreted as Agree), with Improved Trust scoring the highest at 4.11. On the other hand, the negative effects obtained an overall mean score of 3.33 (interpreted as neutral/uncertain), with an Increase of Customer Dissatisfaction scoring the highest at 3.54. The findings also reveal that TikTok is the most prominent social commerce platform among students, with a usage rate of 58%. Therefore, students in Pamantasan ng Lungsod ng Maynila are affected by the fastest growing social media platforms. Furthermore, the study finds no significant difference in the effects of social commerce based on the social media platforms used by students at Pamantasan ng Lungsod ng Maynila. These findings shed light on the influence of social commerce on student buying behavior, offering insights into this emerging form of e-commerce. Keywords: Social Commerce, Improved Trust, TikTok.
Business Research: (BSBA major i Marketing Management) - Pamantasan ng Lungsod ng Maynila, 2023.
Keywords: 2 -- 0; 6; 20; 20; 2